Playing techniques of the nnanga of Buganda - Muehrer, Rachel (International Library of African Music, 2012)
The nnanga is a bowed-neck harp found in the Buganda kingdom, located on Lake Victoria in southern Uganda. At one time groups of musicians resided in the king's royal enclosure, called the lubiri, to perform for the king. Of these musicians, the player of the nnanga had the most candid access to the king. He was the only musician allowed to play privately for the king and his wives. The harp player was also a vocal improviser and poet, and through his song texts he was able to advise and critique the king. The nnanga player was also arguably the sole figure among the court musicians who could produce the repertoire played on all the court instruments.
Keywords: African Music